Contract Farming : Constraints and Limitations - J.R. Mishra and B.B.Singh, (Indian Journal of Extension Education, 2022)
Agriculture is main source of livelihood of the rural population and source of economy of Uttarakhand state. The state has the advantage of producing different off-season vegetables, supply of different kinds of temperate fruits and forest based products. Therefore, to develop the agriculture and to help the farming community, Uttarakhand government has given license to different corporate houses for establishing the agro processing unit and procuring raw materials through contract farming. Presently many companies are involved in contract farming for procuring their raw materials. But contract farmers are facing a lot of constraints while, adopting contract farming. The present study was conducted in two districts of districts of Uttarakhand. i.e. Udham Singh Nagar and Nainital. A total of 150 contract farmers were interviewed from five contract crops viz. Basmati rice, Organic Basmati, Medicinal and Aromatic Plants, Floriculture and Sugarcane. The findings indicated that contract farmers of Uttarakhand faced constraints like small land holding, involvement of greater risk, lack of input available, lack credit,, lack of technical know-how, lack of storage and transportation facility, Lack of crop insurance, lack of printed material, lack of contact person and lack of law to protect farmers.